Challenging conversations with simulated patients - Dennis, Diane; Furness, Anne; Parry, Sharon (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 John Wiley & Sons Ltd and The Association for the Study of Medical Education Background: Simulation-based learning (SBL) activities in the health sciences provide students with opportunities to interact with realistic patients and environments. This study aimed to develop and then implement a novel activity using simulation for a large group of mostly millennial physiotherapy students, to enhance their ability to communicate with a challenging patient and to assess their motivation to learn. Methods: Students enrolled in a second-year communication unit were invited to participate in a non-compulsory unique SBL activity in groups of four for 40 minutes, undertaking two 5-minute simulation scenarios and two debriefing sessions. On completion of the activity, 140 students scored their motivation to learn during the activity using the Instructional Materials Motivation Scale (IMMS) questionnaire. Results: Of the physiotherapy students enrolled in the unit, 83 per cent took part in the SBL and 100 per cent of the participants completed the follow-up survey. Mean scores for each subscale ranged from 3.8 to 4.0, reflecting that students agreed more than moderately with the statements made in the scale. The median total IMMS score for all students was 149, well above the published median total score of the scale (108). Simulation-based learning activities provide students with opportunities to interact with realistic patients and environments. Discussion: The SBL activity model was successfully implemented and received positively by the students in terms of their motivation to learn. It gained the attention of participants by providing an opportunity to practise the non-technical skill of ‘communicating with patients’, previously learned in the classroom, in a simulated realistic environment and by using a design that seemed to consider the needs of the millennial generation.